TRANSFORMASI DESAIN KRIYA BAMBU CURUG MENJADI DESAIN PRODUK YANG MODERN - Gumulya, Devanny (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
ABSTRACT Tangerang Regency since 1800-an to 1900-an is known as the centre of bamboo hats Craft. In 1930 bamboo hats productions were dropped due to declining exports, fashion changes and market competition of South American artisans and the economic crisis that hit the world Export-import. Tangerang regency which used to be known as Handicraft Center is now known as Industrial city because it has several industrial areas and has many labour sources. Folk crafts are regressing due to tight market competition and cause craftsmen to decline. Therefore, it takes efforts to preserve the craft of Tangerang district. One of the reasons for the declining of Curug Bamboo is due to lack of product innovation to meet the market needs, but the living artisans have such an excellent craftsmanship. This makes the young generation in Curug not interested to learn weaving and the craftsmen are at dusk and have no successor generation. The purpose of this research is to add value to the woven bamboo in Panongan District by using transformation method in the design process, as well as preserving Curug bamboo weaving. The transformation is done with morphological chart approach, a visual chart to generate ideas, in which traditional elements are combined with modern elements. In this study will be identified design features of the bamboo Curug bamboo craft, and how these features are transformed into a modern bamboo product design. The result is four homedecor products for the target hotel, where the design still maintains the shape of the hat but is given a modern twist.